Multimodal Analysis of GoFood and GrabFood Advertisements - Siti 'Azizah; Refnaldi Refnaldi (Universitas Negeri Padang, 2022)
This study discussed multimodal analysis of GoFood and GrabFood advertisements. This study is aimed at finding out the linguistic, visual and gestural elements in GoFood and GrabFood advertisements and their differences in representing the concept of online advertising. This study was conducted by using descriptive approach. The data used in this study are the six video advertisements of GoFood and GrabFood which are analyzed by applying Halliday’s Systemic Functional linguistic; Transitivity and mood, Kress and van Leeuwen’s Representational Meaning, and Cheong’s Generic Structure Potential. The data were in the form of text and images. The results of this study show that there are some similarities and differences of the linguistic, visual and gestural analysis between GoFood and GrabFood. The similarities found in the linguistic and gestural analysis between GoFood and GrabFood. Whilts, the differences found in the generic structure and visual analysis of GoFood and GrabFood. This research found that those elements are integrated in GoFood and GrabFood advertisements. In addition, the structure of GSP created in GoFood is a complete one (lead, display, emblem (visual), announcement, enhancer, emblem (linguistic), tag, and call-and-visit information), while GrabFood advertisements use call-and-visit information rarely. Thus, these advertisements involve the concept of online advertising.